Effect of pharmacological and homeopathic substances on Trichodina sp in larvae of red tilapia Oreochromis sp in farming - Serna-Ardila, Mariana (2022)
Parasites are one of the biggest problems affecting fish health, Trichodina sp being the most common in the early life stages of the red tilapia Oreochromis sp. The objective of this study was to evaluate the efficacy of pharmacological and homeopathic substances in the control of Trichodina sp in red tilapia larvae at the Centro Experimental Piscícola (Antioquia, Colombia). In total, 300 red tilapia larvae in the reversion phase (80 observations/larva) were used and distributed in 15 aquariums, each with an effective volume of 63 L. At 0 and 48 hours, two homeopathic substances were applied (garlic [Allium sativum] and ginger [Zingiber officinale], 5 mg/L each) and two pharmacological substances (metronidazole and albendazole, 10 mg/L each) and a control group. The larvae were sedated and the number of Trichodina sp was counted at 0, 48 and 72 h using an optical microscope (4X objective). The use of garlic and metronidazole decreased the total number of parasites counted from 5622 on average to 302 at 72 h (p<0.05), decreasing the prevalence percentage from 100 to 50% and with a larval mortality of 3%. In a second trial to corroborate the efficacy of different doses, it was found that garlic at 20 mg/L had a similar effect to that of metronidazole at 20 mg/L, showing the potential use of homeopathic as a replacement for pharmacological substances. Albendazole caused the death of all red tilapia larvae.